Friday

August 22, 2014

August 22, 2014

Posted by **Sandy** on Sunday, March 16, 2014 at 6:39pm.

y'' + 5y' - 6y = 0 , y(0) = 0 , y(2) = 1

- Calculus -
**Steve**, Sunday, March 16, 2014 at 11:38pmy = c1 e^-6x + c2 e^x

Plug in your boundary conditions, and you get

c1 + c2 = 0

c1/e^12 + c2/e^2 = 1

Now just solve for c1 and c2

**Related Questions**

Differential Equation - Solve the following initial-value problem: y"+6y'+5y=0...

Calculus - Second Order Differential Equations - Solve the boundary-value ...

Pre-Calculus - Find the maximum value of the function for the polygonal convex ...

College Algebra - okay so using y = (-5/6)x + 3 how do i find the corresponding ...

Algebra - I'm really lose with this problem...HELP Using Cramer Rule If D=O use ...

Algebra 2 - maximize p=6x+10y minimize p=14x+9y use elimination to solve: 4x+5y=...

Algebra II - Factor the Polynomial in quadratic form. 6y(to the sixth power) - ...

Math - Consider the initial value problem y'' +5y'+6y=0, y(0)=4.87 and y'(0)=...

algebra 1 - how do you solve the following questions using the substitution ...

Math help - 6y³(2x - 5y² + 8) help solve